2017
DOI: 10.1111/rda.13049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of service number on conception rate in Japanese Black cattle

Abstract: The conception rate (CR) of Japanese Black cattle has been decreasing since 1990. The objectives of this study were to compare CR by artificial insemination (AI) number, and to assess the interaction between AI number and possible factors related to CR in Japanese Black cattle. Records of 11,182 AI records for 6,741 heifers and 61,302 AI records for 13,139 cows on 977 farms were analysed. The average CR of heifers was 47.0%, and CR at the first, second and third AI was higher than at the fourth or subsequent A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 21 publications
(20 reference statements)
3
18
1
Order By: Relevance
“…Resynchronization facilitates greater use of TAI, which is favourable to allow for cross‐breeding, replacement of genetically superior matrices, greater standardization of batches of calves and reduction in the amount of bulls needed. Our results along with the study by Irikura et al, (, ) suggest that future studies on resynchronization, followed by a third AI treatment under tropical conditions, could also aid in maximizing the reproductive efficiency.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Resynchronization facilitates greater use of TAI, which is favourable to allow for cross‐breeding, replacement of genetically superior matrices, greater standardization of batches of calves and reduction in the amount of bulls needed. Our results along with the study by Irikura et al, (, ) suggest that future studies on resynchronization, followed by a third AI treatment under tropical conditions, could also aid in maximizing the reproductive efficiency.…”
Section: Discussionsupporting
confidence: 75%
“…Previous research (Irikura, Uematsu, Kitahara, Osawa, & Sasaki, , ) showed an increase in pregnancy rate after a third artificial insemination (AI). Resynchronization facilitates greater use of TAI, which is favourable to allow for cross‐breeding, replacement of genetically superior matrices, greater standardization of batches of calves and reduction in the amount of bulls needed.…”
Section: Discussionmentioning
confidence: 99%
“…The data we analysed were a subset of a larger data set from a previous study that contained 86,348 artificial insemination (AI) records of 50,482 parity records in 16,746 animals on 1,006 farms raising Japanese Black cattle in Miyazaki between July 2005 and April 2010 (Irikura et al., ). In this study, heifers and cows that failed to be conceived at least once were extracted from the data set to investigate the association of ISI with CR.…”
Section: Methodsmentioning
confidence: 99%
“…Low conception rate (CR) and a failure to detect a cow returning to oestrus after service could extend the interservice interval (ISI) and decrease the efficiency of calf production resulting in economic loss. The CR at first service in Japanese Black cattle, the most common beef cattle breed in Japan also known as “Wagyu,” is approximately 46.5% (Irikura, Uematsu, Kitahara, Osawa, & Sasaki, ), that is about half of cows inseminated need to be reinseminated. Detection of failed inseminations and timely reinsemination of cows is a challenge that can shorten the ISI and improve reproductive efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, livestock animals are bred mainly through artificial insemination. A decrease in the rate of conception is one of the doi: 10.1292/jvms.19-0475 greatest challenges especially for dairy farmers [10,18]. The low conception rate may be attributed to the fertilizing capacity of sperm [28].…”
Section: Discussionmentioning
confidence: 99%